A Guiding Line? Rethinking the Road in American Post-Apocalyptic Narratives - Cécile DO HUU (E-REA)
In the USA, road lines guide both American travel literature and the nation’s history of westward expansion. From western films to road movies, the road has become a specific space-time woven from the mythologies of the Frontier, wilderness, progress, as well as an imaginary of freedom and new beginnings. However, traditional road representations now face technological advances, environmental consciousness, and global crisis. The rise of post-apocalyptic road narratives signals a genre shift, questioning the myth of universal mobility tied to an ideologic conception of liberty. This study delves into this evolution, analyzing pessimistic yet realistic post-apocalyptic road novels and films like Cormac McCarthy’s The Road, John Hillcoat’s adaptation, Dave Eggers’s Heroes of the Frontier, and Casey Affleck’s Light of my Life. Drawing from Bakhtin’s chronotope theory and the transmedial nature of the road narrative, it investigates how the road operates as a space-time for individual travel tales and the American national narrative, undergoing shifts in mobility, history, and narration. The post-apocalyptic backdrop redefines family ethics within the road narrative, envisioning the road as a space-time for transmitting stories and collective memories.